Emotional and Clinical Challenges of Delayed HIV Seroconversion – Case Study - Farfan Cano, Galo Guillermo; Farfán-Cano, Stanley Guillermo; Farfán-Cano, Harold Reynaldo (Futurity Medicine, 2024)
Aims: to examine the emotional and clinical impact of delayed HIV seroconversion in a 36-year-old male healthcare professional in Ecuador. Methodology: a case report analysis that included patient history, clinical presentation, and treatment outcomes. Results: severe anxiety, depression, and perceived risk of death due to delayed ART initiation. Symptoms of weight loss and profuse sweating resolved after ART and psychiatric treatment. Scientific Novelty: the paper highlights the complexities of delayed HIV diagnosis and its profound emotional impact, emphasising the need for regular testing and comprehensive mental health support. Conclusion: timely HIV testing and integrated medical and emotional care are critical for managing delayed seroconversion.